Local government and biodiversity conservation: a case from the Bolivian lowlands - Kaimowitz, D.; Flores, G.; Johnson, J.; Pacheco, P.; Pavez, I.; Roper, J.M.; Vallejos, C.; Velez, R. (Biodiversity Support Program, 2000)
This case study analyses origins and causes of decentralisation in Bolivia, how the process has affected tropical forest management, and initial impacts of decentralisation on distribution of benefits from forests. Impact of the Popular Participation Law of 1994, which bolstered municipal governments in general, and the Forestry Law of 1996, which gave municipal governments a key role in forest policy is stressed. The study focuses on 40 municipalities in the lowlands with substantial forest resources or important protected areas. It suggests that decentralisation will give groups with the most direct contact with natural resources greater power to decide how to manage them. Decentralisation offers new opportunities for poor rural people in heavily forested municipalities to increase their access to resources, political power, or income. Major obstacles include difficulties in identifying appropriate public forests and weak municipal capacity etc. Most politically and economically important groups have adopted a ‘green discourse’ promoting the environment and natural resource conservation. However, their rhetoric is not matched by their actions, which concern access to existing resources and short-term gains. Many municipal governments have initiated forest management, wilderness conservation, agroforestry, and land use planning activities but these are often under funded, poorly staffed or ill conceived. Efforts to reduce forest clearing and degradation remain good intentions and symbolic actions. In a few cases, municipal governments have led efforts to create protected areas to meet their own local needs but their position on indigenous territorial rights largely depends on the extent of indigenous peoples' political power. Where indigenous people play a strong role in municipal governments, decentralisation has strengthened their territorial claims; otherwise, their claims have been weakened. Local governments require external assistance to strengthen their support for and capacity to promote sustainable resource management. They need a favourable policy context and clear mechanisms for exercising their legal rights and responsibilities but national and departmental government agencies have largely failed to supply them.